2023
DOI: 10.1152/japplphysiol.00692.2022
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical nasal high flow ventilation improves clearance of CO2 from the anatomical dead space and increases positive airway pressure

Abstract: Positive airway pressure that dynamically changes with breathing, and clearance of anatomical dead space are the key mechanisms of noninvasive respiratory support with nasal high flow (NHF). Pressure mainly depends on flow rate and nare occlusion. The hypothesis is that an increase in asymmetrical occlusion of the nares leads to an improvement in dead-space clearance resulting in a reduction in re-breathing. Clearance was investigated with volumetric capnography in an adult upper-airway model, which was ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…These results are consistent with findings recently reported by Tatkov et al who performed a study of the asymmetrical interface in an upper airway model [ 18 ]. They demonstrated improved dead-space clearance and more efficient CO 2 elimination from the upper airway with the asymmetrical interface that was due to the preferential flow of gas out of the lesser occluded nare and redirected flow from the larger cannula to the contralateral nare during expiration.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with findings recently reported by Tatkov et al who performed a study of the asymmetrical interface in an upper airway model [ 18 ]. They demonstrated improved dead-space clearance and more efficient CO 2 elimination from the upper airway with the asymmetrical interface that was due to the preferential flow of gas out of the lesser occluded nare and redirected flow from the larger cannula to the contralateral nare during expiration.…”
Section: Discussionsupporting
confidence: 93%
“…Studying symmetrical interfaces of varying size, Pinkham et al demonstrated that a greater prong area-to-nare area ratio resulted in greater end-expiratory airway pressure in a bench model and that this effect was magnified at higher flow rates [ 23 ]. Tatkov et al reported higher PEEP during support with the asymmetrical interface, particularly at flow rates of 40 and 60 l/min with a maximal difference of 2–3 cmH 2 O [ 18 ]. Vieira et al also reported higher nasopharyngeal pressure at end expiration with the asymmetrical cannula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a new HFNC interface using asymmetrical prongs was approved for clinical practice [ 17 , 18 ]. Unlike standard nasal cannulas with equally sized prongs, the asymmetrical prongs deliver different flow rates between the two nostrils [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%